O‐Phospho‐l‐Serine mediates Hyporesponsiveness toward FVIII in Hemophilia A‐Murine Model by Inducing Tolerogenic Properties in Dendritic Cells. Issue 11 (29th September 2014) - Fathallah, Anas M.; Ramakrishnan, Radha; Balu‐Iyer, Sathy V.
<x xml:space="preserve">Abstract</x> The clinical use of therapeutic proteins can be complicated by the development of anti‐product antibodies. We have previously observed that O‐phospho‐l‐serine (OPLS) reduced antibody response to FVIII in Hemophilia‐A (HA) mice. However, the mechanism underlying this observation is not clear. We hypothesize that OPLS reduces immunogenicity by inducing tolerogenic properties in dendritic cells (DCs). We tested this hypothesis using in vivo, in vitro, and ex vivo methods. Naive HA mice that were pre‐exposed to FVIII in the presence of OPLS showed substantially lower antibody response following rechallenge with OPLS free FVIII as compared with dexamethasone‐pretreated mice. Exposure of OPLS to bone‐marrow‐derived dendritic cells (BMDCs) in culturing conditions resulted in an increase in the regulatory cytokine TGF‐β and a decrease in proinflammatory cytokines TNF‐α and IL12p70. This was accompanied by a significant reduction in upregulation of costimulatory marker CD40, as measured by flow cytometry. Furthermore, ex vivo matured BMDCs in the presence of FVIII and OPLS failed to elicit a robust immune response in HA mice compared with FVIII‐treated BMDCs. Our data suggest that OPLS modulates the immune response by altering the function and maturation of DCs, resulting in the induction of tolerogenic properties. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3457–3463, 2014